A Role for Estrogen Receptor alpha36 in Cancer Progression - Pagano, Maria Teresa; Ortona, Elena; Dupuis, Maria Luisa (Frontiers in Endocrinology, 2020)
Estrogen receptor α (ERα) functions as a ligand dependent transcription factor that directly binds specific estrogen responsive elements, thus regulating the transcription of estrogen sensitive genes. ERα has also been shown to be associated with the plasma membrane (membrane associated ERα, mERα), concentrated in lipid rafts, plasma membrane microdomains with a distinct lipid composition, where it transduces membrane-initiated estrogen-dependent activation of the mitogen-activated protein (MAP) kinase signaling pathway. Two isoforms of ERα have been described: the “traditional” ERα66 (66 kDa) and a lower molecular weight variant: the ERα46 (46 kDa). More recently, a novel ERα variant with a molecular mass of 36 kDa (ERα36) has been discovered. Notably, ERα36 hs been found expressed in different human tumor cells, including both ER- positive and ER- negative breast cancer cells. Estrogen signaling at the cell membrane via ERα36 appears as capable of activating multiple pathways of importance for cancer aggressiveness and metastatic potential. The presence of serum autoantibodies reacting with mERα (anti-ERα Abs) in a large percentage of patients with breast cancer has recently been reported by our group. These anti-ERα Abs seem to act as estrogen agonists rapidly triggering MAP kinase pathway activation thus inducing tumor cell proliferation and overcoming cell resistance to anti-estrogen drug tamoxifen. In this review, we describe the involvement of ERα36 in different tumors. We also report the potential pathogenetic activity of anti-ERα Abs and their implication in drug resistance.